Chlorophyta – plants connected with diverse water reservoirs in the Wielkopolska region (western Poland) - Messyasz, Beata (Biodiversity: Research and Conservation, 2006)
The representatives of Chlorophyta (principally Chlorococcales) play an important role in the algal communities in species composition as well as in number structure. Nevertheless, it should be noted that in all cases the species with the broadest distribution in the Wielkopolska reservoirs were: Desmodsmus subspicatus, D. communis, Scenedesmus naegeli, Monoraphidium contorum, Pediastrum boryanum, P. tetras, P. duplex, Staurastrum gracile, S. paradoxum, Tetraedron minimum, T. caudatum, T. triangulare. At present, Pediastrum simplex, which until recently occurred commonly in the plankton, is now making a smaller contribution to the algae communities. Green algae play an important role in the formation of the algal biodiversity in the investigated water ecosystems. The highest participation of green algae was observed in both shallow lakes and fish ponds while the lowest was in puddles and soil waters which have a tendency to dry up. Monocultures of representatives of the Chlamydomonadales were characteristic of temporary water habitats. The increase of eutrophication and the decline of aquatic habitats are contributing to the reduction of the green algae biodiversity (particularly desmids) of not only the investigated area, but also throughout the country.